Plasticity-Inducing TMS Protocols to Investigate Somatosensory Control of Hand Function - M. Jacobs; A. Premji; A. J. Nelson (Neural Plasticity)
Hand function depends on sensory feedback to direct an appropriate motor response. There is clear evidence that somatosensory cortices modulate motor behaviour and physiology within primary motor cortex. However, this information is mainly from research in animals and the bridge to human hand control is needed. Emerging evidence in humans supports the notion that somatosensory cortices modulate motor behaviour, physiology and sensory perception. Transcranial magnetic stimulation (TMS) allows for the investigation of primary and higher-order somatosensory cortices and their role in control of hand movement in humans. This review provides a summary of several TMS protocols in the investigation of hand control via the somatosensory cortices. TMS plasticity inducing protocols reviewed include paired associative stimulation, repetitive TMS, theta-burst stimulation as well as other techniques that aim to modulate cortical excitability in sensorimotor cortices. Although the discussed techniques may modulate cortical excitability, careful consideration of experimental design is needed to isolate factors that may interfere with desired results of the plasticity-inducing protocol, specifically events that may lead to metaplasticity within the targeted cortex.